Analysis of Liquidity Ratios and Profitability Ratios as Assessment Tools to Measure Financial Performance at PT Indofood Sukses Makmur Tbk - Nurfaedah; A.Muh.Rafly Purnama; Nurhani; Bunyamin; Andi Hadidu (Journal of Digital Business and Global Economy, 2025)
This study aims to determine and analyze liquidity ratios as a measure of financial performance at PT. Indofood Sukses Makmur Tbk for the period 2020-2022. The research method used is descriptive quantitative with data collection techniques through literature studies and documentation in the form of company financial reports for that period. Data analysis was carried out using liquidity ratios and profitability ratios. The results show that in terms of liquidity ratios, the financial performance of PT. Indofood Sukses Makmur Tbk in 2020-2022 based on the current ratio is in fairly good condition, even though the value has not reached the perfect standard of 200%. In terms of the cash ratio, the financial condition is relatively good because it exceeds the standard of 50%. Meanwhile, the quick ratio shows a fairly good condition because it tends to increase every year, even though it declined in one year, but it is still above the general standard. In terms of profitability ratios, the company's financial performance based on gross profit margin is in a very good condition because it has exceeded the standard of 20%. Furthermore, when viewed from the return on equity, the company's financial performance is very low because it does not reach the standard of 40%.